EVALUATING THE TRAINING EFFECTIVENESS OF A “STUDENT LEARNING SUPPORT” SCHEME (Journal of Foreign Language Studies, 2021)
French language teacher training at Ho Chi Minh City University of Education focuses on improving professional capacity through practice modules. With a “Student learning support” scheme, the authors expect to create more opportunities of highly pragmatic professional practice for pedagogic students besides two internship periods at high schools. After seven weeks of implementation, improvements in tutees’ linguistic skills and communication skills as well as positive transformation in the tutors’ perception and professional capacity were recorded.
Keywords: learning support; pedagogy professional training; tutor; tutee; self-training